Desenvolvimento de ambiente integrado para simulação e otimização estática da produção de etanol a partir de bagaço de cana-de-açúcar por rota bioquímica - Furlan, Felipe Fernando (2012)
Sugarcane bagasse is an interesting option for second generation ethanol production. However, its use for this purpose is constrained by the energetic self-suficiency of the industrial plant, apart from the necessary economic considerations, given other possible uses for sugarcane bagasse. It was proposed in this work the development of a tool to assist economic and process-related decisions regarding the production of ethanol from sugarcane juice and bagasse, through stationary simulation and optimization of the first and second generation ethanol production process. A new approach for distillation columns simulation using equation-based simulators was presented, using multilinear interpolation. This approach allowed the simulation of the process of ethanol production, which employs a set of distillation columns for ethanol purification, that would otherwise present convergence problems, especially during the optimization step in which several conditions are tested. Results show that the methodology was able to reproduce the nonlinear behavior of the set of distillation columns with enough precision for the work developed here. The tool was tested for second generation ethanol production using organosolv as pretreatment. The results show that the implemented stochastic optimizer was able to find the optimal condition for an objective function representing the cash ow of the plant, which was confirmed by the contour plots obtained for this function. The tool also allows the analysis of steam consumption distribution for each section of the industrial plant, which enables the determination of the impact of second generation ethanol production on the general process.